ANALISIS DIAMETER KAWAT SPRING DAN PANJANG LOWER MOUNTING SUSPENSI BELAKANG MOTOR MATIC - listiyono listiyono; Nurhadi - Nurhadi; Khambali Khambali (Polinema Press, Politeknik Negeri Malang, 2021)
The stability of the vehicle / motorbike is also determined by the suspension. Usually the suspension on the motor is installed right-left symmetrically. This is so that the vehicle load is evenly distributed if there is a shock / sudden load. But development and need negate each other. Currently, the development of automatic motorbikes is quite rapid. This motorbike is designed to be sleek and nimble and easy to maintain. Therefore, the rear suspension of the automatic motorbike is installed on only one side. And this usually occurs during sharp turns and high speeds and if you go through uneven roads. For this reason, it is necessary to design the right suspension so that the vehicle can maintain stability even when turning or passing uneven roads. This instability is due to the large vibration of the vehicle. The objectives of this study are 1. To determine the effect of the size of the spring wire and the length of the mounting on the vibration frequency. 2. Find the diameter of the spring wire and the length of the mounting that will give a good vibration frequency. This study uses the Desaign Of Experiment method. Desaign factor 2, namely diameter of spring wire and length of muoting. Level 3 factor is 6 mm, 7 mm and 8 mm diameter. Mounting lengths of 30 mm, 35 mm and 40 mm. Data analysis using MINITAB program. From the analysis, it is found that 1. The diameter of the spring coil wire and the mounting has a significant effect on the vibration frequency of the automatic motor. 2. The best size for wire spring diameter for coil spring motor matic is 7 mm, while the thickness of the mounting is 37 mm. Keywords: Suspension, Motorcycle, Spring Wire. Lower Mounting, vibration frequency